NILAI, GAGASAN, STRATEGI, DAN IMPLEMENTASI PENDIDIKAN MODERASI BERAGAMA DALAM KEHIDUPAN SEHARI-HARI DAN DI LINGKUNGAN KAMPUS - Syifa Azzahra; Trisnawati, Olivera Zalianti, Widya Priyantik, Ihsan Nurizzati, Sriliza (Adisam Publisher, 2026)
Religious moderation is an important idea in maintaining the harmony of the lives of the pluralistic Indonesian people. Diversity of religions, cultures, and views of life is the wealth of the nation, but it also has the potential to cause conflict if it is not accompanied by mutual respect and balanced religious understanding. Therefore, religious moderation education is the main strategy in forming a religious attitude that is fair, tolerant, and rejects all forms of extremism. Religious moderation education not only emphasizes the aspect of understanding religious teachings, but is also oriented towards the formation of moderate character and behavior in daily life. Religious moderation values such as tolerance, justice, balance, and national commitment need to be internalized through a systematic and sustainable educational process. In daily life, religious moderation education plays a role in creating harmonious and peaceful social relationships. Meanwhile, in the campus environment, religious moderation education is the foundation for building an inclusive, dialogical, and free academic climate from radicalism. With the implementation of the right educational strategy, religious moderation is expected to be able to strengthen unity and maintain the integrity of the nation in the midst of diversity.